Electrical Conductivity of Eclogitic Omphacite and Garnet at Water-Rich Conditions - Liu, Hanyong; Yang, Xiaozhi (Frontiers in Earth Science, 2022)
Electrical conductivity of water-rich omphacite and garnet in eclogite was measured at 1 GPa and 200–800°C in a piston cylinder press and by a Solartron-1260 impedance/gain-phase analyzer at 106-1 Hz frequency. The water content of pre-annealed omphacite and garnet was 775–2,000 and 705–1,460 ppm H2O, respectively. Sample chemistry and water contents remained unchanged during conductivity runs. At otherwise identical conditions, the conductivity of both minerals increases with both temperature and water content, and the water content exponent is ∼1.45 and 1.12 for omphacite and garnet, respectively. The activation enthalpy is ∼70 kJ/mol for omphacite and 84 kJ/mol for garnet and is broadly independent of sample water content. Combining with previous work, the conductivity dependence of omphacite on water content differs between water-rich and water-poor conditions, due to different types and mobility of water in samples that are closely related to its incorporation mechanism; in contrast, the conductivity dependence of garnet with a similar type of water is comparable over a wide range of water contents. The estimated bulk conductivity of eclogite at water-rich conditions is very high, up to ∼0.01–0.1 S/m at 600–900°C. Geophysically resolved high resistivity of subducting crusts at 70–120 km depth suggests extremely low water contents of omphacite and garnet in the eclogitized slab. The data provide support to the model based on omphacite and garnet conductivity at water-poor conditions that the amount of water recycled by crust subduction to the deep mantle is probably limited.